2005
DOI: 10.1007/s10620-005-2800-9
|View full text |Cite
|
Sign up to set email alerts
|

15th Anniversary of Rebamipide: Looking Ahead to the New Mechanisms and New Applications

Abstract: Rebamipide, a gastro-protective drug, was developed in Japan for the treatment of peptic ulcer disease. It was proven superior to the former same category drug cetraxate in a randomized, controlled, double-blind, comparative clinical study in 1989. Rebamipide's mechanisms of actions are different from anti-secretory drugs; it accelerates and improves the quality of ulcer healing and reduces ulcer recurrence rate. Numerous studies have been conducted to explain the mechanisms responsible for these actions, 37 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
96
0
18

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 41 publications
2
96
0
18
Order By: Relevance
“…On the other hand, compounds with different (i.e., non-PG) chemical structures but similar mucosal protective activity to PGs [mucosal protective agents (MPAs)] have been developed in Japan, and some of the MPAs, irsogladine (IRS) (Ueda et al, 1984a,b) and rebamipide (REB) (Uchida et al, 1985;Yamasaki et al, 1987), are now used as antiulcer drugs for the treatment of gastric ulcer and gastritis as gastroprotective agents in Japan and other Asian countries (Arakawa et al, 2005;Hiraishi et al, 2010;Naito Yoshikawa, 2010;Akagi et al, 2013). It has been reported that IRS protects the gastric mucosa by enhancing mucosal integrity through facilitation of gap junctional intracellular communications (Ueda et al, 1995) and suppression of superoxide production by increasing the cAMP level via inhibition of phosphodiesterase (Kyoi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, compounds with different (i.e., non-PG) chemical structures but similar mucosal protective activity to PGs [mucosal protective agents (MPAs)] have been developed in Japan, and some of the MPAs, irsogladine (IRS) (Ueda et al, 1984a,b) and rebamipide (REB) (Uchida et al, 1985;Yamasaki et al, 1987), are now used as antiulcer drugs for the treatment of gastric ulcer and gastritis as gastroprotective agents in Japan and other Asian countries (Arakawa et al, 2005;Hiraishi et al, 2010;Naito Yoshikawa, 2010;Akagi et al, 2013). It has been reported that IRS protects the gastric mucosa by enhancing mucosal integrity through facilitation of gap junctional intracellular communications (Ueda et al, 1995) and suppression of superoxide production by increasing the cAMP level via inhibition of phosphodiesterase (Kyoi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Rebamipide has been reported to act as an anti-inflammatory agent in both acute and chronic inflammation and has an inhibitory effect on proinflammatory cytokines (McCarthy et al, 2003). It exerts protective effect against gastric mucosal inflammation induced by Helicobacter pylori by inhibiting neutrophil function (Yoshida et al, 1996;Aihara et al, 1998;Arakawa et al, 2005). Main functions of rebamipide include mucus glycoprotein synthesis and stimulation of prostaglandin, inhibition of reactive oxygen species, inflammatory cytokines, and chemokines, and inhibition of neutrophil activation (Arakawa et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Rebamipide, a mucosal protective agent, has various actions for ulcer healing and prevention of gastric damage induced by non-steroidal anti-inflammatory drugs and Helicobacter infections (28,29). The mechanisms of anti-ulcer and cytoprotective actions of rebamipide are mainly divided into the following 3 types: 1) acceleration of ulcer healing based on the induction of prostaglandin synthesis via COX-2 expression (30 -32) and its receptor (33) and up-regulation of growth factor and its receptors such as epidermal growth factor (EGF) (34), vascular endothelial growth factor (VEGF) (35), and hepatocyte growth factor (HGF) (36); 2) cytoprotective activities such as induction of mucus secretion (37); 3) anti-inflammatory activities such as free-radical scavenging effect (38 -40), inhibition of neutrophil activation, and migration (41,42) and inhibition of cytokines production from leukocytes (43).…”
Section: Introductionmentioning
confidence: 99%